2018
DOI: 10.1111/cns.13039
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous activities in baroreflex afferent pathway contribute dominant role in parasympathetic neurocontrol of blood pressure regulation

Abstract: The data from current investigations establish a new concept for the role of Ah-type baroreceptor/baroreceptive neurons in controlling blood pressure stability and provide a new pathway for pharmacological intervention for hypertension and cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…From an anatomical standpoint, the ADN in normotensive female rats shows less axonal myelination and smaller cross-sectional area compared with males, and females further express a unique population of low-threshold slow-conducting myelinated afferents known as Ah-type afferents [30,31]. These afferents have nonoverlapping electrophysiological properties and chemical sensitivities of both myelinated A-type and unmyelinated C-type baroreceptor afferents [30,31] and specifically display greater frequency and larger amplitude of spontaneous excitatory postsynaptic currents compared with inhibitory postsynaptic currents [32]. Specific to male and female SHRs, the persistent hypertensive state is commonly associated with smaller myelinated (A-type) and unmyelinated (C-type) axonal cross-sectional area within the ADN, thinner myelin sheath around myelinated axons, and smaller number of unmyelinated fibers in both male and female SHRs relative to normotensive controls [33][34][35], and while morphological and functional characteristics of Ah-type afferent fibers have never been studied in female SHRs, it is possible that similar pathological changes in this fiber subset may underlie the abrogated laterization phenomenon in female SHRs.…”
Section: Discussionmentioning
confidence: 99%
“…From an anatomical standpoint, the ADN in normotensive female rats shows less axonal myelination and smaller cross-sectional area compared with males, and females further express a unique population of low-threshold slow-conducting myelinated afferents known as Ah-type afferents [30,31]. These afferents have nonoverlapping electrophysiological properties and chemical sensitivities of both myelinated A-type and unmyelinated C-type baroreceptor afferents [30,31] and specifically display greater frequency and larger amplitude of spontaneous excitatory postsynaptic currents compared with inhibitory postsynaptic currents [32]. Specific to male and female SHRs, the persistent hypertensive state is commonly associated with smaller myelinated (A-type) and unmyelinated (C-type) axonal cross-sectional area within the ADN, thinner myelin sheath around myelinated axons, and smaller number of unmyelinated fibers in both male and female SHRs relative to normotensive controls [33][34][35], and while morphological and functional characteristics of Ah-type afferent fibers have never been studied in female SHRs, it is possible that similar pathological changes in this fiber subset may underlie the abrogated laterization phenomenon in female SHRs.…”
Section: Discussionmentioning
confidence: 99%
“…The results from qRT-PCR and western blot analysis showed that VEGF mechanosensitive channels (PIEZONs) [26] at baroreceptor terminals of aorta, the converted action potential discharge (bioelectric signals ) from the blood pressure changes (mechanical signals) can be propagated to the 1st-order baroreceptor neurons with the cell bodies housed in the NG [27][28]. The signals are then relayed through their central projections to the medial NTS [29][30][31]…”
Section: Expression Alterations Of Vegf/vegfrs In the Kidney Of Rvh Ratsmentioning
confidence: 99%
“…The autonomic nerve system (ANS) is the key player in the blood pressure (BP) homeostasis via the balance between sympathetic (cardiac afferents) and parasympathetic (vagal afferents), in which vagal inputs dominate this balance by rendering negatively feedback reflexed control mechanism, the baroreflex (BRx) plays a major role in the neurocontrol of both short‐term and long‐term BP regulation. BRx afferent loop initiates the sensing BP fluctuation by baroreceptor terminals distributed in the aorta 1 operated by mechanosensitive PIEZOs channels 2 , 3 , 4 to the cell body of the 1 st ‐order neurons 5 , 6 in the nodose ganglia (NG), and then to the cell body of the 2 nd ‐order neurons 7 , 8 in the nucleus tractus solitarius (NTS) by forming the synapses through its central projection and the efferent loop innervates to the heart and blood vessel. Extensive animal studies have demonstrated that BRx afferent function is critical to stabilize the BP under physiological and hypertensive conditions, 7 , 9 , 10 , 11 , 12 , 13 , 14 suggesting that dysfunction of BRx afferent function is crucial for the development of both primary and secondary hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…BRx afferent loop initiates the sensing BP fluctuation by baroreceptor terminals distributed in the aorta 1 operated by mechanosensitive PIEZOs channels 2 , 3 , 4 to the cell body of the 1 st ‐order neurons 5 , 6 in the nodose ganglia (NG), and then to the cell body of the 2 nd ‐order neurons 7 , 8 in the nucleus tractus solitarius (NTS) by forming the synapses through its central projection and the efferent loop innervates to the heart and blood vessel. Extensive animal studies have demonstrated that BRx afferent function is critical to stabilize the BP under physiological and hypertensive conditions, 7 , 9 , 10 , 11 , 12 , 13 , 14 suggesting that dysfunction of BRx afferent function is crucial for the development of both primary and secondary hypertension.…”
Section: Introductionmentioning
confidence: 99%